METODE PEMBELAJARAN DISKUSI DAN SOROGAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KITAB FATH AL-QORIB - Aliudin Aliudin; Eneng Muslihah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2019)
This study aims to determine; 1) the implementation of the discussion method at the Attoyyibiyyah Islamic Boarding School, Cikande, Serang Regency 2) the implementation of the sorogan method at the Attoyyibiyyah Cikande Islamic Boarding School, Serang Regency 3) the contribution of the discussion and sorogan methods to improve the ability to read the book of fath al-qorib. 4) Comparison of the contribution of the discussion and sorogan methods to improve the ability to read the book of Fath al-qorib. This research is a mixed method research method. Respondents were 40 students, collecting data using questionnaires and tests to determine the contribution of increasing the ability to read the book of fath al-qorib. The qualitative data analysis technique used is the data triangulation technique, while the quantitative data uses statistical analysis. The results of this study are; 1) The discussion method is carried out three times a week, namely; every Saturday night, Monday night and Wednesday night at 20.00 WIB - 22.00, the book that is studied is the book